Integrating Weed Management Strategies to Reduce Seed Production and Viable Seed Dispersal in Kansas Soybean Production - Taylor Lambert; K.B. Jeremie Kouame (Kansas Agricultural Experiment Station Research Reports, 2025)
The management of Palmer amaranth (Amaranthus palmeri) is a challenge in Kansas soybean production, particularly due to its high seed production, persistence in the soil seedbank, and herbicide resistance concerns. Harvest Weed Seed (HWSD) control strategies have shown promise in mitigating this issue by targeting weed seeds during harvest. A field trial assessed the effectiveness of herbicide programs and cover crops on Palmer amaranth biomass and seed production, and the effectiveness of the HWSD in reducing Palmer amaranth seed viability in soybean fields. Results indicated that the herbicide programs were not different in their impact on biomass and seed production. In contrast, use of cover crops reduced the biomass and seed production ≥ 50%. Also, HWSD significantly reduced the viability of Palmer amaranth seeds exiting the back of the combine when the seed control unit was engaged (93% non-viable seed), contributing to a more effective seedbank management practice.
Keywords: Palmer amaranth; soybean; harvest weed seed control